Investigation and Numerical Simulation of the Acoustic Target Strength of the Underwater Submarine Vehicle - Kaveripakam Sathish; Rajesh Anbazhagan; Ravikumar Chinthaginjala Venkata; Fabio Arena; Giovanni Pau (Inventions, 2022)
Modern weapon systems’ survival hinges on their detection capabilities more than anything else. In the active sonar equation, the acoustic target strength is crucial. Under the assumption of plane wave propagation, the standard target strength equation is used to forecast the reradiated intensity for the far field. The ability of a submarine to remain unnoticed while on patrol or accomplishing a mission is its primary defense. Sonar, sometimes known as sound navigation ranging, is a popular method for locating submarines. This is because saltwater effectively absorbs radio frequencies. Sonar technology is used in more than just the commercial fishing business; it is also used in undersea research. The submarine’s designers consider the reflection of acoustic waves to minimize the amount of space required for such reflections. The Target Strength (TS) metric is used to assess the sonar objects’ size. This manuscript explains and demystifies the Benchmark Target Echo Strength Simulation (BeTTSi) benchmark submarine’s TS analysis. This model’s Pressure Acoustic-Boundary Element Model (PA-BEM) interface has been stabilized, and the model itself is pretty huge acoustically.